2018
DOI: 10.3390/fluids3040086
|View full text |Cite
|
Sign up to set email alerts
|

A Hybrid Approach for Model Order Reduction of Barotropic Quasi-Geostrophic Turbulence

Abstract: We put forth a robust reduced-order modeling approach for near real-time prediction of mesoscale flows. In our hybrid-modeling framework, we combine physics-based projection methods with neural network closures to account for truncated modes. We introduce a weighting parameter between the Galerkin projection and extreme learning machine models and explore its effectiveness, accuracy and generalizability. To illustrate the success of the proposed modeling paradigm, we predict both the mean flow pattern and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 88 publications
0
25
0
Order By: Relevance
“…The BVE model shares many features with the twodimensional Euler and Navier-Stokes equations and has been extensively used over the years to describe various aspects of the largest scales of turbulent geophysical fluid dynamics [80][81][82][83][84][85]. Using β−plane assumption reasonable for most oceanic flows, the dimensionless vorticitystreamfunction formulation of the forced-dissipative BVE can be written as [52]:…”
Section: Single-layer Quasi-geostrophic (Qg) Ocean Circulation Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…The BVE model shares many features with the twodimensional Euler and Navier-Stokes equations and has been extensively used over the years to describe various aspects of the largest scales of turbulent geophysical fluid dynamics [80][81][82][83][84][85]. Using β−plane assumption reasonable for most oceanic flows, the dimensionless vorticitystreamfunction formulation of the forced-dissipative BVE can be written as [52]:…”
Section: Single-layer Quasi-geostrophic (Qg) Ocean Circulation Modelmentioning
confidence: 99%
“…Hence, in our study, we utilize numerical schemes suited for simulation of such type of ocean models and for long-time integration. Details of the relevant numerical discretization schemes, Poisson solver, and problem definitions for this study can be found in elsewhere [52,78,88].…”
Section: Single-layer Quasi-geostrophic (Qg) Ocean Circulation Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…The above correction term can be learned with datadriven machine learning algorithm [28,43]. We employ long-short term memory architecture [44], a variant of recurrent neural network to learn this correction.…”
Section: Evolve-then-correct Approachmentioning
confidence: 99%
“…Until recently, the fully non-intrusive modeling can be considered most attractive enabling methodology to do real-time simulation very efficiently in the context of emerging digital twin technologies [103]. In a complimentary fashion, the hybrid models [104][105][106][107][108][109] are developed by combining the intrusive and non-intrusive models in such way that the limitation of one component modeling strategy can be addressed by the other component model.…”
Section: Introductionmentioning
confidence: 99%